Factors associated with the number of microorganisms on the tongue surface in patients following acute stroke. (4th September 2020) - Furuya, Junichi; Beniya, Akane; Suzuki, Hiroyuki; Hidaka, Rena; Matsubara, Chiaki; Obana, Michiyo; Yoshimi, Kanako; Yamaguchi, Kohei; Hara, Koji; Nakagawa, Kazuharu; Nakane, Ayako; Tohara, Haruka; et al.
Abstract: Background: Oral hygiene management of patients with acute stroke is important for preventing aspiration pneumonia and ensuring oral intake. The tongue coating score can be useful for evaluating the oral hygiene level since it reflects the microorganism number on the tongue surface in elderly patients. However, the relationship between the number of oral microorganisms and the tongue coating score in patients with acute stroke remains unclear. Objectives: We aimed to investigate the relationships between the microorganism number on the tongue surface and oral factors, including tongue coating score, tongue surface moisture level and tongue function. Methods: This cross‐sectional study enrolled 73 patients with acute stroke who were hospitalised at an acute care hospital and underwent dental intervention. Potential explanatory factors, including sex, age, Glasgow Coma Scale score, tongue coating score, tongue surface moisture level, nutrition intake method, number of functional teeth and tongue function, were evaluated. Logistic regression analysis determined their association with the microorganism number on the tongue surface. Results: The tongue coating score (odds ratio: 1.31) and tongue surface moisture level (odds ratio: 1.10) were significantly associated with increased microorganism numbers on the tongue surface. Conclusion: The tongue coating score, which reflects the actual number of microorganisms on the tongue surface, could be an effective tool for evaluating oral hygiene level in patients with stroke. Moreover, reducing oral microorganisms in saliva through oral hygiene management, including removing the tongue coating, could contribute towards the prevention of aspiration pneumonia.